Answer:
A. h(x)=4x+2
Step-by-step explanation:
Because it's shifted to the left, you would subtract three units from 5, resulting in 4x+2. Hope this helps, have a nice day! :)
Answer:
The first and the second equation is flipped... meaning you have to switch their places
Step-by-step explanation:
I think I did this before so good luck...
The nth taylor polynomial for the given function is
P₄(x) = ln5 + 1/5 (x-5) - 1/25*2! (x-5)² + 2/125*3! (x-5)³ - 6/625*4! (x - 5)⁴
Given:
f(x) = ln(x)
n = 4
c = 3
nth Taylor polynomial for the function, centered at c
The Taylor series for f(x) = ln x centered at 5 is:
![P_{n}(x)=f(c)+\frac{f^{'} (c)}{1!}(x-c)+ \frac{f^{''} (c)}{2!}(x-c)^{2} +\frac{f^{'''} (c)}{3!}(x-c)^{3}+.....+\frac{f^{n} (c)}{n!}(x-c)^{n}](https://tex.z-dn.net/?f=P_%7Bn%7D%28x%29%3Df%28c%29%2B%5Cfrac%7Bf%5E%7B%27%7D%20%28c%29%7D%7B1%21%7D%28x-c%29%2B%20%20%5Cfrac%7Bf%5E%7B%27%27%7D%20%28c%29%7D%7B2%21%7D%28x-c%29%5E%7B2%7D%20%2B%5Cfrac%7Bf%5E%7B%27%27%27%7D%20%28c%29%7D%7B3%21%7D%28x-c%29%5E%7B3%7D%2B.....%2B%5Cfrac%7Bf%5E%7Bn%7D%20%28c%29%7D%7Bn%21%7D%28x-c%29%5E%7Bn%7D)
Since, c = 5 so,
![P_{4}(x)=f(5)+\frac{f^{'} (5)}{1!}(x-5)+ \frac{f^{''} (5)}{2!}(x-5)^{2} +\frac{f^{'''} (5)}{3!}(x-5)^{3}+.....+\frac{f^{n} (5)}{n!}(x-5)^{n}](https://tex.z-dn.net/?f=P_%7B4%7D%28x%29%3Df%285%29%2B%5Cfrac%7Bf%5E%7B%27%7D%20%285%29%7D%7B1%21%7D%28x-5%29%2B%20%20%5Cfrac%7Bf%5E%7B%27%27%7D%20%285%29%7D%7B2%21%7D%28x-5%29%5E%7B2%7D%20%2B%5Cfrac%7Bf%5E%7B%27%27%27%7D%20%285%29%7D%7B3%21%7D%28x-5%29%5E%7B3%7D%2B.....%2B%5Cfrac%7Bf%5E%7Bn%7D%20%285%29%7D%7Bn%21%7D%28x-5%29%5E%7Bn%7D)
Now
f(5) = ln 5
f'(x) = 1/x ⇒ f'(5) = 1/5
f''(x) = -1/x² ⇒ f''(5) = -1/5² = -1/25
f'''(x) = 2/x³ ⇒ f'''(5) = 2/5³ = 2/125
f''''(x) = -6/x⁴ ⇒ f (5) = -6/5⁴ = -6/625
So Taylor polynomial for n = 4 is:
P₄(x) = ln5 + 1/5 (x-5) - 1/25*2! (x-5)² + 2/125*3! (x-5)³ - 6/625*4! (x - 5)⁴
Hence,
The nth taylor polynomial for the given function is
P₄(x) = ln5 + 1/5 (x-5) - 1/25*2! (x-5)² + 2/125*3! (x-5)³ - 6/625*4! (x - 5)⁴
Find out more information about nth taylor polynomial here
brainly.com/question/28196765
#SPJ4
Answer:
yo mama
Step-by-step explanation:
Answer:
Step-by-step explanation:
Let x = length
Then width = (1/2)x
Perimeter = 2(length) + 2(width) = 54
length + width = 27
So, x + (1/2)x = 27
(3/2)x = 27
x = 27(2/3) = 18 (1/2)x = 9
Answer: length = 18 cm and width = 9 cm